Preventing Cyber Espionage for Social Security Stability - Hendri Waluyo Lensa; Marwan Mas'ud; Teguh Dwi Prayoga (FiTUA: JURNAL STUDI ISLAM, 2026)
Cyber espionage, referring to efforts by certain parties to illegally obtain strategic information through digital means, poses a serious threat to human survival and social stability. This issue can be objectively examined from the perspective of the Prophet’s Hadith and maqāṣid al-sharī‘ah. This study employs a qualitative approach using a library research method. The data utilized are secondary and analyzed through descriptive analysis. The theoretical framework applied includes Critical Discourse Analysis (CDA) and the theory of maqāṣid al-sharīʿah, with conclusions drawn using a deductive approach. The results indicate that, from the perspective of maqāṣid al-sharīʿah, cyber espionage undermines societal welfare and violates the five essential objectives: religion, life, intellect, progeny, and wealth. This practice threatens safety, causes economic losses, disrupts education and public services, and diminishes moral and ethical values in society, making its prevention a collective obligation. Prevention can be carried out through the application of Hadith, which emphasizes trustworthiness, commitment to promises, and protection of rights, as well as through CDA to build moral awareness, strengthen digital governance, promote ethical education, and enforce just laws, thereby maintaining social stability and public welfare in the digital era.